Gender transformation in the academy - Berheide, Catherine White; Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Advances in gender research, 2014)
Gender inequality/inequity in the academy has been evidenced globally as women outnumber men seeking degrees in institutions of higher education, but remain concentrated in the lower faculty ranks and absent from administrative positions, particularly in the science, technology, engineering and mathematics (STEM) disciplines The chapters in this volume document the gender inequality in higher education in the United States as well as in Australia, Austria, Portugal, South Africa, and Sweden. They explore the reasons for it and test or suggest remedies. Several are based on projects funded by the U.S. National Science Foundation (NSF), which seeks to address the issue as it is evidenced in STEM disciplines through ADVANCE, a program developed to increase the participation and advancement of women in these disciplines. The authors consider womens situation in the context of a variety of types of educational settings including community colleges, primarily undergraduate institutions, and research-intensive universities.